LibQUAL 2004 : instrumen pengukuran jurang kualiti perkhidmatan Perpustakaan Sultanah Zanariah, Universiti Teknologi Malaysia - Muhamad Akhir, Siti Fatimah (2008)
Academic libraries are facing two major challenges which are global digital environment and increasing competetion. They must improve the quality of their services in order to survive. Alternative approches to measure quality emerge in the business sector. Specifically, through marketing research the SERVQUAL has evolved as an instrumen to measure service quality and what customers value as important. Modification on library settings, LibQUAL was developed as an instrumen to measure quality services by Zone of Tolerance (Service Adequacy Gap and Superiority Gap) according to various group of user need of library. The objective of this research were identifying level of service quality at Perpustakaan Sultanah Zanariah from customers perspective and to determine most desired and critical dimension of quality services. Sampling of 129 postgraduate and 153 undergraduate revealed that different of minimum expectation, perception and expectation. The finding of this research is determined which dimension of service quality is critical required for improvement across all the three dimension of â€œLibQUALâ€? instrument; affected of services, personal control and library as a place.